Three Dimensional Solar Cells Based on Optical Confinement Geometries - Li, Yuan.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Three dimensional (3D) optical geometries are becoming more common in the literature and lexicon of solar cells. Three Dimensional Solar Cells Based on Optical Confinement Geometries describes and reveals the basic operational nuances of 3D photovoltaics using three standard tools: Equivalent Circuit Models, Ray Tracing Optics in the Cavity, and Absorber Spectral Response. These tools aide in understanding experimental absorption profile and device parameters including Jsc, Voc, Fill Factor, and EQE. These methods also apply to individual optical confinement geometry device, integrated optical confinement geometry device, and hybrid optical confinement geometry device. Additionally, this book discusses the importance of these methods in achieving the goal of high efficiency solar cells and suggests a potential application in large-scale photovoltaics businesses, like solar farms.
Introduction -- Equivalent Circuit -- Optical Path in Cavity -- Spectral Response -- Individual Optical Confinement Geometry Device -- Integrated Optical Confinement Geometry Device -- Hybrid Optical Confinement Geometry Device -- Conclusion -- Appendices.
Keywords: Physics; Electric engineering; Renewable energy sources; Physics; Optics, Optoelectronics, Plasmonics and Optical Devices; Energy Technology; Semiconductors; Energy Systems; Renewable and Green Energy